REPRESENTATION ON THE CONCEPT PROFESSION IN ENGLISH FOLK RIDDLES - Shonazarova Gulnoza Shukhrat kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract.  This study examines the representation of the profession concept in English folk riddles from semantic and linguocultural perspectives. Riddles are analyzed as cognitively complex paremiological units that encode meaning through indirect nomination, metaphorical description, and functional semantics. The research demonstrates that profession-related riddles do not explicitly name occupations; instead, they construct professional identity through characteristic actions, tools, clothing, responsibilities, and social roles.